Attributes of News about Firms: An Analysis of Firm-Specific News Reported in the Wall Street Journal Index - II, Robert B. Thompson; Olsen, Chris; Dietrich, J. Richard (Journal of Accounting Research, 1987)
Robert B. Thompson II, Chris Olsen, J. Richard Dietrich, Attributes of News about Firms: An Analysis of Firm-Specific News Reported in the Wall Street Journal Index, Journal of Accounting Research, Vol. 25, No. 2 (Autumn, 1987), pp. 245-274